The polymerization efficiency of a bulk-fill composite based on matrix-modification technology - Tarek M. Elshazly; Christoph Bourauel; Moustafa N. Aboushelib; Dalia I. Sherief; Dalia I. El-Korashy (Restorative Dentistry & Endodontics)
ObjectivesTo evaluate the polymerization efficiency of a matrix-modified bulk-fill composite, and compare it to a conventional composite which has a similar filler system. The degree of conversion (DC%) and monomer elution were measured over different storage periods. Additionally, fillers' content was examined.Materials and MethodsCylindrical specimens were prepared, in bulk and incrementally, from Filtek Bulk Fill (B) and Filtek Supreme XTE (S) composites using a Teflon mold, for each test (n = 6). Using attenuated total reflection method of Fourier transformation infrared spectroscopy, DC% was measured after 24 hours, 7 days, and 30 days. Using high-performance liquid chromatography, elution of hydroxyethyl methacrylate, triethylene glycol dimethacrylate, urethane dimethacrylate, and bisphenol-A glycidyl dimethacrylate was measured after 24 hours, 7 days and 30 days. Filler content was examined by scanning electron microscopy (SEM). Data were analyzed using 2-way mixed-model analysis of variance (α = 0.05).ResultsThere was no significant difference in DC% over different storage periods between B-bulk and S-incremental. Higher monomer elution was detected significantly from S than B. The elution quantity and rate varied significantly over storage periods and between different monomers. SEM images showed differences in fillers' sizes and agglomeration between both materials.ConclusionsMatrix-modified bulk-fill composites could be packed and cured in bulk with polymerization efficiency similar to conventional composites.